Aligning an undergraduate psychological medicine subject with the mental health needs of the local region - Rikard-Bell, Christopher; Woolley, Torres (BMC medical education, 2018)
The James Cook University (JCU) medical school recently revised its Year 2 human development and behaviour module to be more relevant and practical for students, and more aligned with the mental health priorities of the local region (north Queensland). This study reports medical students' level of preparedness conferred by the re-designed 'Psychological Medicine and Human Development' (PMHD) subject for their later 4-week, rural clinical placement in Year 2. Non-randomized, controlled 'naturalistic' study with pre- and post-intervention surveys. The patient mental health experiences of Year 2 students who went on clinical placement after undertaking the PMHD subject were compared to those who went on placement before undertaking PMHD. A total of 209 JCU Year 2 medical students completed surveys from a possible 217 (response rate = 96%). Compared to students whom had not taken PMHD before going on placement, students going on placement after undertaking PMHD were significantly more likely to report: feeling comfortable discussing mental health issues with patients (p = 0.001); being prepared for mental health discussions with patients (p < 0.001); having an actual mental health discussion with a patient (p < 0.001); and, volunteering an opinion on the appropriateness of their supervising doctor's response (p < 0.001). Students reported subject content involving information and classroom instruction on assessing and interviewing patients for mental illness to be of most use. Providing medical students with psychological medicine information on locally prevalent mental health conditions plus practical classroom experiences in conducting mental state exams better prepares them for interacting with patients experiencing psychological distress. This novel methodology - aligning formal teaching in a subject with an evaluation utilizing a proximate student placement to provide useful feedback on the curriculum content and assess the relevance of the material taught - could be used to revise other content areas of a medical course to be more locally relevant and practically focused, and then to evaluate the success of this revision.